Analisis Keterkaitan Konsep Dasar Geografi di Kelas 4 Sekolah Dasar - Zunika Agung Rahayu (CV. Supernova Office Stationary and Printing, 2024)
This research aims to analyze the relationship between the basic concepts of social studies material in the geography branch in social studies learning at elementary school level in the independent curriculum which includes distribution, elements, CP, and learning orientation/scope of material. The presentation method used is literature review from various relevant study sources. This literature review includes several literature from relevant research, including regulations for implementing the independent curriculum, articles in relevant journals, books and other literature related to the independent curriculum. Based on the results of the analysis of the relationship between the basic concepts of geography in grade 4 elementary school which have been included in the phases, the science and social sciences are very broad and the combination of science and social studies is still not optimal. However, in terms of optimization, Social Sciences can stand alone as a subject because the branches of social science are so broad.